The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1063/1.1488580
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of anomalous volume behavior of water–benzene mixtures in the vicinity of the critical region

Abstract: Volume behavior of water–benzene mixtures at temperatures and pressures in the 473–623 K and 100–350 bar ranges, respectively, has been studied by infrared in situ measurements. The densities of the benzene-rich phase were estimated from the spectroscopically determined concentrations of water and benzene and compared with the average densities before mixing, which were calculated using literature densities of neat water and neat benzene at the same temperature and pressure. Anomalously large volume change for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…Figure 10 shows plots of the maximum values at a few temperatures against molar fraction of benzene. The previously reported values for the benzene-rich phase 21 are also plotted in Fig. 10 and prove to be consistent with the present results for the water-rich phase.…”
Section: Composition Dependence Of the Relative Volume Changesupporting
confidence: 80%
See 2 more Smart Citations
“…Figure 10 shows plots of the maximum values at a few temperatures against molar fraction of benzene. The previously reported values for the benzene-rich phase 21 are also plotted in Fig. 10 and prove to be consistent with the present results for the water-rich phase.…”
Section: Composition Dependence Of the Relative Volume Changesupporting
confidence: 80%
“…For example, volume expansion on the mixing of water and benzene becomes as large as 300% at 573 K and 100 bar. 21 Similar phenomena have been observed for water-toluene and water-ethylbenzene mixtures. 22 Thus the anomalous volume expansion is considered to be common to the mixing of water and hydrophobic hydrocarbons in the vicinity of the critical region.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar volumetric behavior has recently been reported by Wormald and Hodgetts [8] on mixtures of carbon dioxide and sulfur hexafluoride in the near-critical region. Another intriguing pattern of volumetric behavior has been reported by Furutaka and Ikawa [9] and Jin and Ikawa [10] for water-benzene mixtures at high temperatures and pressures. They have estimated molar concentrations of water and benzene in each of the two coexisting two phases of their mixtures by measuring infrared and near-infrared absorption intensities, and found that the relative volume change on mixing becomes anomalously large in the vicinity of the critical region.…”
Section: Introductionmentioning
confidence: 89%
“…To compare the volumetric behavior of the water-methanol mixtures with that of water-benzene mixtures, we estimate the relative volume change given by the following expression [9,10]:…”
Section: Relative Volume Changementioning
confidence: 99%